The secret world of Arrietty [videorecording (Blu-Ray + DVD)] - Miyazaki, Hayao, 1941-; Suzuki, Toshio, 1948 August 19-; Yonebayashi, Hiromasa, 1973-; Mendler, Bridgit; Henrie, David, 1989-; Poehler, Amy, 1971-; Arnett, Will; Arias, Moises, 1994-; Burnett, Carol; Kirkpatrick, Karey; Norton, Mary (2010)
In a secret world hidden beneath the floorboards, little people called Borrowers live quietly among us. This film tells the story of Arrietty, a young Borrower. She eventually befriends Shawn, a human boy who is living with his great aunt, Sadako. When Sadako's maid, Haru, becomes suspicious of the floorboard's disturbance, Arrietty and her family must escape detection, even if it means leaving their beloved home.